Site dilution in SrRuO3: effects on structural and magnetic properties. (3rd February 2017) - Gupta, Renu; Pramanik, A K
Abstract: We have investigated the effect of site dilution with substitution of nonmagnetic element in SrRu1− x Ti x O3 ( x   ⩽  0.7). The nature of ferromagnetic state in SrRuO3 is believed to be of itinerant type with transition temperature T c ∼ 162 K. Crystallographically, SrRuO3 has a distorted orthorhombic structure. Substitution of T i + 4 (3 d 0 ) for Ru +4 (4 d 4 ), however, does not introduce significant structural modification due to their matching ionic radii. This substitution, on the other hand, is expected to tune the electronic correlation effect and the d electron density in the system. With Ti substitution, we find that magnetic moment and Curie temperature decreases but T c remains unchanged which has been attributed to opposite tuning of electron correlation effect and density of states within the framework of itinerant ferromagnetism. The estimated critical exponent ( β ) related to magnetization implies a mean-field type of magnetic nature in SrRuO3 . The value of β further increases with x which is understood from the dilution effect of magnetic lattice. The system evolves to exhibit Griffiths phase like behavior above T c which is usually realized in diluted ferromagnet following local moment model of magnetism. Our detail analysis of magnetization data indicates that magnetic state in SrRuO3 has contribution from both itinerant and local moment model of magnetism.